An Overview on Power System Load Sharing Approaches (International Journal of Innovative Research in Engineering & Management, 2021)
Load shedding refers to a system for which electric energy  demand is distributed among several power sources. Load  shedding is used to reduce the strain on the energy source to the  greatest extent possible when the energy demand exceeds what  the power source can supply. A service provider sells power to a  client. Traditional load shedding methods, and even under voltage  regulation, have a longer reaction time and are inconsistent in  properly distributing load in the case of any interruptions or  failures. This causes an increase or reduction in load, resulting in  an inability to meet the energy demand. The study, titled  Intelligent Load Shedding, focused on a more contemporary  approach to load shedding. A thorough comparison of  conventional versus intelligent load shedding methods was  conducted from the perspectives of operation design, engineering  and implementation. It consumes remained revealed that the  intelligent technique of load shedding overcomes all of the  disadvantages of traditional techniques, is extremely efficient,  and requires very little maintenance.
Keywords: Controller; Frequency Relay; Load Shedding; Monitoring; Simulation; Traditional Load Shedding